Circulating antibody and memory B-cell responses to C. difficile toxins A and B in patients with C. difficile- associated diarrhoea, inflammatory bowel disease and cystic fibrosis - Monaghan, Tanya M.; Robins, Adrian; Knox, Alan; Sewell, Herbert F.; Mahida, Yashwant R. (Public Library of Science, 2013)
C. difficile infection (CDI) is rarely reported in cystic fibrosis (CF) patients despite frequent hospitalisations and antibiotic usage. Conversely, the prevalence of CDI in inflammatory bowel disease (IBD) has received increased attention. We investigated components of the IgG-specific humoral immune response to C. difficile toxins A and B in patients with C. difficile-associated diarrhoea (CDAD), IBD patients with CDI, CF patients and healthy controls. Serum anti-toxin IgG was determined by ELISA. Circulating antigen-activated B-cells were investigated using Alexa Fluor 488-labelled toxin A and assessed by flow cytometry. Following induction of differentiation of memory B-cells, toxin A- and B-specific antibody secreting cells (ASCs) were quantified using ELISpot. We present the first data showing levels of serum anti-toxin A and B antibodies were significantly higher in patients with CF (without a history of CDI) than in CDAD patients and were stably maintained over time. Notably, the CDAD patients were significantly older than the CF patients. We also show that circulating toxin A-specific memory B-cells (IgD-negative) can be detected in CDAD patients [0.92 (0.09–1.78)%], and were prominent (5.64%, 1.14%) in two CF patients who were asymptomatic carriers of C. difficile. There was correlation between toxin A- and B-specific ASCs, with significantly higher proportions of the latter seen. In some with CDAD, high serum antibody levels were seen to only one of the two toxins. Mucosal secretion of toxin-specific IgG was detected in an additional group of IBD patients with no history of CDI. We conclude that enhanced and stable humoral immune responses to toxins A and B may protect CF and some IBD patients against CDI. The impaired ability to generate strong and/or sustained toxin-specific antibody and memory B-cell responses may increase susceptibility